Engineering of SauriCas9 with enhanced specificity - Xiaoqi Zhang; Chen Tao; Miaomiao Li; Sufang Zhang; Puping Liang; Yan Huang; Huihui Liu; Yongming Wang (Molecular Therapy: Nucleic Acids)
SauriCas9 is a compact Cas9 nuclease showing promise for in vivo therapeutic applications. However, concerns about off-target effects necessitated improvements in specificity. We addressed this by introducing mutations to eliminate polar contacts between Cas9 and the target DNA, resulting in the SauriCas9-R253A variant with enhanced specificity. To validate its efficacy, we employed SauriCas9-R253A to disrupt three genes (B2M, TRAC, and PDCD1), a strategy integral to the development of allogeneic chimeric antigen receptor T cell (CAR-T) therapies. Our results demonstrated that the most efficient single-guide RNAs for SauriCas9-R253A exhibited comparable activity to SpCas9 and showed no detectable off-target effects in the disruption of these genes, highlighting its therapeutic potential.